Creativity in Islamic Religious Education: A Qualitative Study on the Development and Implementation of Digital Comics in Primary Schools - Riza, Muslikh; ANwar, Moh; Sutomo, Moh (Program Studi PGMI, 2025)
This study aims to explore the development and implementation of digital comic media in Islamic Religious Education (IRE) at SDN No. 4 Tuban Kuta Badung. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation. The findings indicate that the use of digital comics as a learning medium improves students’ motivation, understanding of Islamic values, and active participation in the learning process. Visual narratives that are relatable to students’ daily lives support the internalization of moral values such as honesty, responsibility, and tolerance. Teachers also experienced enhanced creativity in designing digital-based instruction. This study concludes that digital comics are an effective medium for Islamic education at the elementary level and can serve as a strategic alternative for delivering engaging, contextual, and relevant religious instruction in the digital era.